Antifeedant Activity of Leaf Aqueous Extracts of Selected Medicinal Plants on VI Instar Larva of Helicoverpa Armigera (Hubner) - Ravi, G.; Sundararajan, Dr.G. (International Journal of Scientific Research and Management (IJSRM), 2020)
Phytochemicals, especially botanical insecticides are currently of interest because of their successful application in plant protection as biocontrol agents. Biological activity of leaf aqueous extract of ten selected medicinal plants were evaluated against the fourth-instar larvae of gram pod borer Helicoverpa armigera (H¨ubner), (Lepidoptera: Noctuidae). Antifeedant activity of leaf aqueous extracts of Abutilon indicum L., Achyranthus aspera L., Aerva lanata L., Albiziz amara (Roxb), Andrographis paniculata Ness., Cardiospermum halicacabum L., Cassia tora L., Catharanthus roseus L (G) Don., Datura metal L. and Tribulus terrestris L. were evaluated in this study. Preliminary screening after 24 h of exposure with leaf aqueous extracts of the selected plants at a concentration of 1,000 ppm exhibited significant larval mortality rate. The percentage mortality rate ranged considerably from 10.8 to 72.8. The mortality rate was observed in the decreasing order of A. paniculata > C. roseus > D. metal > A. amara > C. halicacabum > A. indicum > C. tora > T. terrestris > A. aspera >A. lanata against the larvae of H. armigera. The results imply that leaf aqueous extract of A. paniculata, C. roseus and D. metal can potentially be used as eco-friendly pest control agents against the larva of H. armigera.